Effect of bio-carrier filling rate on oxygen transfer coefficient of different diffusers in MBBR process. Issue 39 (20th August 2016) - Sun, Lifeng; Zhang, Feng; Liu, Changqing; Bi, Xuejun; Cheng, Lihua; Li, Shuai; Liu, Ying; Qiao, Zhong
Abstract: This paper mainly discussed the effect of bio-carrier filling rate on the oxygen transfer coefficient of different diffusers in the MBBR process. The results show that bio-carriers could increase the oxygen transfer coefficients of the microporous diffusers both in clean water and in mixed liquor because of the shearing effect that created microbubbles and enhanced microscopic hydrodynamic flow regime of the reactor. Compared to the test without bio-carriers, dosing bio-carriers could increase the oxygen transfer coefficient of microporous membrane diffuser by 10.78% in clean water and 10.17% in mixed liquor. Dosing bio-carriers could increase the oxygen transfer coefficient of the campanulate corundum aerator and perforated pipe more than the microporous membrane diffuser. Compared to the control, dosing bio-carriers could increase the K La of campanulate corundum aerator and perforated pipe diffuser by almost 13.40 and 17.74% in clean water, and 10.97 and 20.14% in mixed liquor, respectively.